Validation of a flexible multibody belt-drive model - Čepon, Gregor (Strojniški vestnik, 2011)
In the past decade the applicability of belt-drives has been extended significantly due to their increased reliability. With automotive engines it is now common to join a large number of belt-drives into a single, long belt-drive with several tensioner pulleys. However, these belt-drives can exhibit complex dynamic behaviors; therefore it is very important to predict the dynamics response of such systems using validated numerical models. The aim of this paper is to perform the validation of a developed belt-drive model. The validation of this belt-drive model was performed using a two-pulley belt-drive. The numerically obtained results are compared with experimental data under various operational conditions. Finally, the applicability of the belt-drive model is presented by simulating a serpentine belt-drive, considering non-steady, belt-drive operational conditions.
Keywords: absolutni vozliščni koordinatni sistem; ANCF; angular speed loss; belt-drive; jermenska gonila; serpentinsko jermensko gonilo; validacija; validation